Inner Areas, University, and Territorial Cohesion in Italy: The Sicilian Case Study - Luigi Scrofani; Gianni Petino; Arturo Di Bella; Alessandro Arangio (Bollettino della Società Geografica Italiana)
In the current paper the authors used the STeMA methodology, adopted in PRIN 2015 Programme and applied to Italian inner areas to check the impact of European and Italian policies to get the objective of territorial cohesion. At first the authors provide a synthesis of scientific and institutional debate on inner areas and inner peripheries. Then they use three indicators, according to the TIA approach, to audit the contributions of important local development factors, such University and three-years graduates. They also studied the policies of cohesion and territorial development in Sicily in planning 2014-2020. Finally, the authors outline some initial reflections on the state of the research carried out and on the necessity for a redesign of the complex relationship between university and territory, as a strategic aspect of the more general national policies for territorial cohesion.